PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI PADA MATERI BERFIKIR KOMPUTASIONAL X TKJT SMK N 1 PAINAN - Muhammad Ikhsan Rusdi; Heri Mulyono; Bernediv Nurdin (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
The low level of students’ interest and achievement in computational thinking at SMK N 1 Painan has become one of the challenges in the learning process. This issue arises due to the use of conventional teaching methods that are less interactive and often make students feel bored. Therefore, this research aims to develop educational game-based learning media as an innovative alternative to enhance students’ motivation, interest, and understanding of computational thinking concepts. This research applied the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The educational game was developed using Unity and Visual Studio Code, featuring interactive materials through levels, quizzes, and scoring systems. The validity of the game was assessed by three media experts, while its practicality was tested by teachers and Grade X TJKT students at SMK N 1 Painan. The results show that the media obtained an average validity score of 87.93%, categorized as very valid. The practicality test yielded an average of 89.57% from teachers and 86% from students, categorized as very practical. Thus, the developed educational game is considered feasible to be used as a learning medium and effective in improving students’ motivation and understanding of computational thinking material.